The Effect of Local Government Revenue (LGR), Transfer Income, Capital Expenditures On Economic Growth Before and During Covid-19 Pandemic: Pengaruh Pendapatan Pemerintah Daerah (PAD), Pendapatan Transfer, Belanja Modal Terhadap Pertumbuhan Ekonomi Sebelum dan Saat Pandemi Covid-19 - Ghiffari, Panji Muhammad; Ariani, Kurnia Rina (Universitas Muhammadiyah Sidoarjo, 2022)
Economic growth is an important goal for local and central governments. Economic growth encourages local governments to carry out economic development by managing existing resources and forming a partnership pattern with local communities in order to create new jobs that will affect the development of economic activities in the area. This study aims to analyze the effect of Local Government Revenue (LGR), Transfer Income, Capital Expenditure on Economic Growth in districts and cities in Central Java Province before and during Covid-19 pandemic. The data used in this study is secondary data from a total of 35 districts and cities (29 districts and 6 towns) in Central Java province obtained from BPS and DJPK Central Java. By using multiple regression analytic, and differential test this study shows that LGR, transfer income, and capital expenditures have an effect on economic growth and there is no significant difference in economic growth before and during the covid-19 pandemic in districts and cities in the province of Central Java.